THE EFFECT OF PROVIDING LOCAL ADDITIONAL FOOD ON THE WEIGHT OF TODDLERS BELOW THE RED LINE IN THE BATANG LUPAR KAPUAS HULU HEALTH CENTER - Aspia Lamana; Dina Setyani; Lydia Febri Kurniatin (Jurnal Medicare, 2025)
BGM toddlers can disrupt the growth and development of children, leading to malnutrition, severe malnutrition, and even stunting. One way to overcome this problem is by providing supplementary local food. This study is to analyze the effect of providing local food on the weight of toddlers below the red line in the Batang Lupar Health Center, Kapuas Hulu Regency. Quasi-experimental research design with one group pre-test–post-test design. The intervention in this study was local supplementary food in the form of processed snakehead fish given with 7 different menus for 28 days. This study was conducted in the Batang Lupar Health Center. The population in this study was 30 toddlers with BGM. The sampling technique was total sampling. This study was conducted by evaluating the weight gain of BGM toddlers before and after the intervention. The analysis in this study was bivariate with the paired T-test. The results showed that there was an effect of providing local supplementary food on the weight of toddlers below the red line, as indicated by the average weight value before the intervention of 9,920 and after the intervention of 10,120, while the mean difference value was 0.2000 (p-value 0.000 < 0.05). In conclusion, providing local supplementary food has a significant effect on the weight gain of BGM toddlers.